Acute Kidney Injury (AKI) Prerenal pada Dengue Shock Syndrome - I.B. Aditya Nugraha; Wayan Sudhana (Cermin Dunia Kedokteran, 2018)
Dilaporkan satu kasus pasien laki-laki usia 12 tahun dengan diagnosis awal severe dengue syndrome dengan acute kidney injury (AKI) stadium II pre-renal. Diduga ada kaitan antara DBD dan kejadian AKI. A case of 12 year-old boy diagnosed as Severe Dengue Syndrome with acute kidney injury (AKI) pre-renal stage II was reported. Relationship of dengue and AKI was discussed.